The influence of auditor and auditee on mandatory audit fees in France - Ben Larbi, Sami; Ebondo Wa Mandzila, Eustache; Meniaoui, Jihène; Tapia Moor, Ernesto (GECONTEC: Revista Internacional de Gestión del Conocimiento y la Tecnología, 2024)
This study employs a pluralistic theoretical framework, integrating the Resource-Based View, neo-institutional, and governance theories, to identify factors explaining joint audit fees. Utilizing a panel dataset of 116 firms over six years (totaling 696 observations) in France, we apply an extension of generalized linear models to handle non-independent observations. Considering both auditor quality and audited company characteristics, our research expands previous studies on French audit fees, which have predominantly focused on auditor quality. We find that joint audit fees are influenced by firm size, audit team composition, sector of activity, and client company size and director count. However, factors such as the choice of internal control framework, separation of control and management functions, and proportion of independent directors do not significantly impact joint audit fees.